Videofluoroscopic Evaluation of the Pharynx and Upper Esophageal Sphincter in the Dog: A Systematic Review of the Literature - Pollard, Rachel E. (Frontiers in Veterinary Science, 2019)
Background: Diseases of the pharynx and upper esophageal sphincter can result in debilitating respiratory difficulty, dysphagia or a combination of both. An exact diagnosis is essential to properly prognosticate and guide therapy. Videofluoroscopic assessment of the pharynx and upper esophageal sphincter with or without orally administered contrast material is the diagnostic of choice for many diseases as both anatomic and functional information is gleaned. The purpose of this review is to assess for continuity in imaging protocols across institutions and to record quantitative and qualitative parameters used for analysis of videofluoroscopy of the pharynx and upper esophageal sphincter in dogs. Methods: A systematic literature search was performed including articles published in peer-reviewed veterinary journals involving the topic of videofluoroscopy of the pharynx and upper esophageal sphincter through August 1, 2018. Specifics of study acquisition technique were recorded. Quantitative and qualitative videofluoroscopic parameters were recorded and compared across institutions where appropriate using one-way ANOVA with p ≤ 0.05 being considered significant. Results: Videofluoroscopy of the pharynx and upper esophageal sphincter is performed either in right lateral or standing postures depending on the institution. Bolus size and consistency used during contrast videofluoroscopy of swallowing differs between institutions. Some institutions evaluate videofluoroscopic studies using qualitative criteria while others apply quantitative measures. Reported quantitative measures include inter-swallow interval, swallow rate, jaw cycles per swallow ratio, time to upper esophageal opening, maximal pharyngeal contraction, maximum laryngeal excursion, upper esophageal closure, epiglottic re-opening, and pharyngeal constriction ratio. Measurement outcomes are significantly different between institutions and when bolus size/consistency is variable when assessing healthy dogs. Conclusions: The current peer-reviewed literature on fluoroscopic evaluation of the pharynx and UES in dogs shows a lack of standardization regarding imaging protocol. There is not a standard set of quantitative criteria applied amongst the institutions and there are significant differences in the outcomes obtained from videofluoroscopic assessment of swallowing suggesting significant inter-observer or inter-institutional variability. A consensus statement regarding imaging protocol and what parameters should be used to interpret airway and swallowing videofluoroscopic studies of the pharynx and UES in dogs is needed along with targeted analysis of observer variability.